2015
DOI: 10.1242/dev.121046
|View full text |Cite
|
Sign up to set email alerts
|

Rab8a vesicles regulate Wnt ligand delivery and Paneth cell maturation at the intestinal stem cell niche

Abstract: Communication between stem and niche supporting cells maintains the homeostasis of adult tissues. Wnt signaling is a crucial regulator of the stem cell niche, but the mechanism that governs Wnt ligand delivery in this compartment has not been fully investigated. We identified that Wnt secretion is partly dependent on Rab8a-mediated anterograde transport of Gpr177 (wntless), a Wnt-specific transmembrane transporter. Gpr177 binds to Rab8a, depletion of which compromises Gpr177 traffic, thereby weakening the secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 137 publications
(218 reference statements)
1
52
1
Order By: Relevance
“…Blocked Paneth cell maturation seen in this study is echoed by at least another recently reported knockout mouse model in which the crypt Wnt signaling activity was weakened because of a reduced Wnt ligand secretion 7, 8. The enhanced colitis susceptibility shown in G αq/11 DKO mice suggests that the mucosal regenerative program induced by the chemical injury probably increased the cellular demands for G αq/11 -mediated signaling activities in the intestine.…”
supporting
confidence: 56%
“…Blocked Paneth cell maturation seen in this study is echoed by at least another recently reported knockout mouse model in which the crypt Wnt signaling activity was weakened because of a reduced Wnt ligand secretion 7, 8. The enhanced colitis susceptibility shown in G αq/11 DKO mice suggests that the mucosal regenerative program induced by the chemical injury probably increased the cellular demands for G αq/11 -mediated signaling activities in the intestine.…”
supporting
confidence: 56%
“…However, in Int-G q /G 11 DKO mice, mRNA levels of EphB3 and EphB2 were not altered (Supplementary Figure 2). Rab8a knock-out mice have been reported recently 40 . Wnt secretion is regulated partly by Rab8a-mediated anterograde transport.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the adult stem cell population requires β-CATENIN-dependent WNT signaling (“canonical” WNT signaling, herein referred to as WNT/β-CATENIN signaling). Inhibition or loss of WNT/β-CATENIN signaling in the epithelium results in loss of stem cells in the crypt (Chiacchiera et al., 2016, Das et al., 2015, Farin et al., 2012, Pinto et al., 2003, Valenta et al., 2016), while activating mutations leading to constitutive WNT activation are causative in colorectal cancer (Barker et al., 2009, Fearon and Spence, 2012, Fearon and Wicha, 2014, Korinek et al., 1997, Morin et al., 1997). Unlike the plethora of information about regulation of the adult ISC, it is much less clear whether and when WNT/β-CATENIN signaling plays a role in the embryonic intestine, and in particular we understand very little about intestine development prior to the formation of villi.…”
Section: Introductionmentioning
confidence: 99%